The Influence of Perception Factors, Situation Factors and In-Object Factors on the Quality of Educational Services at SMP Negeri 17 Kota Kupang - ARISKA, Vivi Evyanti; DJAHA, Ajis Salim Adang; MAS'AMAH, Mas'amah (PT Keberlanjutan Strategis Indonesia, 2023)
Mathematics is a very important subject. Various schools show that the importance of mathematics lessons is not matched by students' absorption of the material, so that the results of learning mathematics for most students in Indonesia are not optimal, as happened at SMP Negeri 17 Kota Kupang. Limited facilities and infrastructure in schools have an impact on the learning process and student perceptions of the quality of service in schools, especially student perceptions on the service quality of mathematics teachers at SMP Negeri 17 Kota Kupang. The purpose of this study was to analyze the influence of perception factors, situational factors, and internal factors on the quality of education services by mathematics teachers at SMP Negeri 17 Kota Kupang. The population in this study were all 8th and 9th grade students at SMP Negeri 17 Kota Kupang, totaling 126 students. Number of samples in this study amounted to 56 students who were taken using a stratified random sampling technique. This research includes the type of associative research using a quantitative approach (positivistic). The research instrument used was a questionnaire with 25 statement items. Based on the data analysis of the results of the study, the perception factor (X1), situation factor (X2), factor in the object (X3) on the quality of teacher service (Y), shows an Adjusted R 2 (Adjusted R Square) value of 0.266 (26.6%) ) implies that the influence of perceiving factors (X1), situational factors (X2), factors in objects (X3) on the quality of teacher service (Y), is 26.6%